Pendampingan Kelompok Mahasiswa dalam Memanfaatkan Marketplace dan Online Shop Sebagai Media Pemasaran Produk Inovasi Pesantren - Sudriyanto Sudriyanto; Isti Ghulam Hidayatullah; M. Alman David; Putri Tsamrotul Fu’adiyah; M. Fajar Santoso; M. Lukman Hakim (Universitas Nurul Jadid, 2021)
Based on the results of a survey report from the Indonesian Internet Service Providers Association (AP JII) on June 2-25, 2020, the total number of Indonesian internet users is 73.7 percent or 196,714,070.3 million people from the total population in Indonesia of 266,911,900 people. . Fenomina is currently using the internet as a means of promotion for online marketing. Many companies are so implementing online sales that it has had an impact on the decline in the turnover of otheer companies that are still offline. The purpos of this activity is to improve the skills and knowledge of companies and students so they can implement marketplace-based online sales. The essence of this activity with one day of training to create a marketplace account and online marketing asistance for a full month. It is hoped that with this training, partner companiies and students can advance and develop their online marketplacee-based sales independently. The training model with one day followed by one month of mentoring is expected to be areference for similar activities.